The State and Prospects of the Customs Union of the Republic of Belarus, Republic of Kazakhstan and Russian Federation - Natalia A. Vorontsova (Московский журнал международного права, 2014)
The integration processes in the modern world develop continually: states associate in different economic organizations, they broaden or stay in stagnation. At present the process of new members’ accession to the Customs Union and Single Economic Space of the Republic of Belarus, Republic of Kazakhstan and Russian Federation takes place. In this article the author analyzes the legal basis of the Customs Union, offers the model (structure) of a Program on the accession of candidate states to the Customs Union, describes the required measures and examines the conception of “the roadmap”.